PENYEBAB DAN PENANGANAN PLAGIARISME DI KALANGAN MAHASISWA PENDIDIKAN MATEMATIKA - Tiara Kusuma Astuti; Itoh Nur Sari; Karniasih Ramadhani; Syifa Restania Putri; Zulkardi Zulkardi; Novita Sari (BIBLIOTIKA : Jurnal Kajian Perpustakaan dan Informasi, 2021)
This study aims to know the cause and prevent plagiarism for mathematics education students. The method in this study isqualitative with a literature study analysis technique approach. This study shows thatthe causes of plagiarism are the low self-confidence in writing works with their own thoughts, bad habits in learning, and think that doesn’t lead to learning process.